Designing intercultural space. A multi-scalar approach in the Albergheria neighbourhood in Palermo - Federico Wulff Barreiro; Renzo Lecardane; Paola La Scala (Agathón)
Migration has always been a major driver of urban transformation stimulating opportunities and challenges for cities and encouraging architectural and urban designers for taking a proactive and dynamic role in responding to the crisis. Enhancing these changes, and designing intercultural spaces for local communities, is a complex and urgent spatial challenge, that should be addressed by a multi-scalar approach aiming to integrate urban, architectural and public spaces. This paper illustrates a research-action resulting from a collective work developed on key urban spaces of the Albergheria neighbourhood of Palermo, where a design-led research based on a multi-scalar regeneration approach (urban, architectural and public space) can reframe the role of architecture and spatial practices as agents of social, intercultural inclusion and spatial reactivation at different scales.